2019
DOI: 10.21203/rs.2.12905/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Users’ Acceptance of Electronic Patient Portals in Lebanon

Abstract: Background Acceptance of Electronic patient portal (EPP) is instrumental for its success. Studies on users’ acceptance in the Middle East region are scarce. This study aims to explore factors influencing users’ acceptance of EPP, both patients and providers, at a tertiary care center in Lebanon using the Technology Acceptance Model (TAM). We concurrently test the internal construct validity and the reliability of the TAM. Methods A cross-sectional survey design and the vignette approach were used. For validati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For example, in Lebanon, recent reports suggest high internet penetration rates (29) and widespread smartphones use (30). In addition, a previous study on user acceptance of patient portals in Lebanon reported that about half of the sampled population reported a signi cant intent to use the portal (24). Given that the intention to use was lower than that reported in the Western literature, the authors feared even lesser actual app utilization rates (24,31).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in Lebanon, recent reports suggest high internet penetration rates (29) and widespread smartphones use (30). In addition, a previous study on user acceptance of patient portals in Lebanon reported that about half of the sampled population reported a signi cant intent to use the portal (24). Given that the intention to use was lower than that reported in the Western literature, the authors feared even lesser actual app utilization rates (24,31).…”
Section: Introductionmentioning
confidence: 92%
“…Engagement could be incorporated into the patient education section as most participants did not use the patient education section. A study conducted among patients in the same institution before the implementation of the portal has shown that perceived usefulness had more predictive value than perceived ease of use on the intention to use the patient portal (24). Although the frequency of app use was not signi cantly associated with the total uMARS score, it was positively associated with the subjective quality score.…”
Section: App Qualitymentioning
confidence: 97%